The Influence of Religiosity Leaderships Practices towards the SMEs Business Performance in Food and Beverages Industry - Ezanee Mohamed Elias; Norlila Mahidin; Ahmad Yusni Bahaudin (International Journal of Supply Chain Management, 2019)
The objective of the study is to examine the influence of religiosity leadership’s practices among the top management people of halal food and beverages SMEs towards their business performance. Previous studies have shown that religiosity practices among the leaders or top management people in the enterprises has contributed a significant impact to the business performance. Some results show these people, which influenced by religiosity has motivated their colleagues and workers to perform job very well that contribute to improve business performance. This study applied a quantitative design with a simple random sampling and survey questionnaire were distributed to 370 respondents by emails. The obtained data were analyzed by Smart-PLS. The findings of the study have a different result as it was hypothesized. The results of this study show that the characteristics of religiosity practiced by SMEs in Malaysia has been insignificantly affected the SMEs’ business performance. This indicates that religiosity practices among the top management people are not a driver or a factor that can be relied on to improve their business performance either from financial or non-financial aspects. Perhaps the future study can collaborate with other variables such as entrepreneurial orientation (EO). Thus, it might give a different result since the (EO) is a significant factor to increase the SMEs’ business performance.